The bond behavior between concrete and corroded steel bar under repeated loading. (1st June 2017) - Lin, Hongwei; Zhao, Yuxi; Ožbolt, Joško; Hans-Wolf, Reinhardt
Highlights: The coupled effect of corrosion and repeated loading on bond was investigated. Empirical equation for the fatigue life of bond of deformed steel bars was derived. Bond model for RC members subjected to corrosion and cyclic loading was suggested. Abstract: Repeated loading can affect the serviceability of RC structures by causing the bond deterioration. In the present study a series of pull-out tests have been carried out to investigate the bond deterioration due to the repeated loading of corroded reinforcement. The specimens were corroded to different corrosion level and subjected to repeated loading for various stress levels and loading cycles. The test results showed that the bond behavior under repeated loading was characterized by progressive increase of residual slip. The slip increase became more pronounced when the stress level was increased. The comparison with monotonic test results indicated that the repeated loading exhibited no significant influence on the bond strength and on the slip at peak bond stress for both corroded and non-corroded specimens. It was also found that the corrosion could lead to an increase of applied stress levels, which resulted in the substantial decrease of the fatigue life of bond. Through systematic evaluation of the test data a model for bond stress-slip relationship under repeated loading was proposed. Moreover, empirical equation for the fatigue life of bond of corroded reinforcement was also derived.